2016
DOI: 10.15226/jnhfs.2016.00162
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms, Loss of Appetite and Under Nutrition among Treated HIV Patients: A Cross Sectional Study in Goma, the Democratic Republic of Congo

Abstract: Background: The study explored the association between the depressive symptoms, loss of appetite and under nutrition among treated HIV patients in Goma, a post conflict setting. Methodology: This was a cross-sectional survey carried out from February 1 st to March 3 rd , 2016. The prevalence of depressive symptoms and loss of appetite were estimated. A logistic regression model was used to identify the associations between under nutrition, loss of appetite and depressive symptoms, adjusted for other covariates. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…46,48 Moreover, the finding of study conducted in Congo in 2016 revealed a positive association between depression and loss of appetite. 8 This result implies the need to establish intervention and strengthen programs that target psychosocial problems and nutritional status in PLHIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46,48 Moreover, the finding of study conducted in Congo in 2016 revealed a positive association between depression and loss of appetite. 8 This result implies the need to establish intervention and strengthen programs that target psychosocial problems and nutritional status in PLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…4 Studies done in developing countries reported that the prevalence of malnutrition among HIV-infected adults ranges from 19.4% in Tanzania to 43% in Brazil. [5][6][7][8] SSA is the most affected part of the world among the 37.9 million people living with HIV globally, the majority are from low-and middleincome countries with an estimate of 68%. 9 Studies in different parts of Ethiopia reported high prevalence of malnutrition among people living with HIV enrolled on Anti-Retroviral Therapy (ART).…”
Section: Introductionmentioning
confidence: 99%